Hubungan Pola Asuh, Pengetahuan dan Sikap Ibu dengan Pencegahan Stunting Pada Balita di Posyandu Tunas Segar 4 - Suwandewi, Alit; Azidin, Yustan; Khalilati, Noor; Aprilia, Hanura; Daud, Izma; Salamiah, Dea (Journal of Nursing Invention, 2024)
Background: Stunting is a problem in children from an early age due to chronic malnutrition in the womb which is caused by inadequate nutritional intake, so that children appear shorter than children their age. The problem of stunting is still encountered in the Pekauaman Community Health Center working area, Banjarmasin City. Objective: This research is to determine the relationship between parenting patterns, knowledge and attitudes of mothers with the prevention of stunting in toddlers at Posyandu Tunas Segar 4, Kelayan Selatan District, Banjarmasin.Method: This research design uses cross-sectional correlation analysis. In this study, a simple random sampling technique was used to select 66 mothers who had toddlers aged 0-59 months. In this research, the independent variables are the mother's parenting style, knowledge and attitudes. The dependent variable is stunting prevention behavior, which is measured through a questionnaire sheet with an r value >0.361, tested using Spearman rank analysis with p value = 0.05.Results: Research shows that maternal parenting patterns, maternal knowledge and attitudes are related to preventing stunting in toddlers. The results of the analysis of parenting patterns p value = -0.010, knowledge = -0.022 and attitude = -0.109. Conclusion: The conclusion from the results of this research is that there is a relationship between parenting patterns, knowledge and attitudes of mothers and the prevention of stunting in toddlers at Posyandu Tunas Segar 4, Kelayan Selatan District, Banjarmasin. Advice is expected for mothers who have toddlers to routinely follow the posyandu schedule.